О зарождении и росте кристаллов W в закрытых реакторах при восстановлении его из оксида WO₃ водородом - Бондаренко, В.П.; Андреев, И.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Exploration effects of legitimacies of particles propagation of a tungsten powder surveyed.
It is shown, that over growth rate of tungsten particles on different reduction stages is dominated
with different limiting factors.